The Effect of Using The “Lollipop Stick” Strategy for Active Learning on The Achievement of Tenth Graders in The Subject of History - Sabir Sabir Abdullrahim Awla; Hamed Mustafa Belbas; Faraidun Abdullrahim Abdulla (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
This study aims to identify the effect of using the ice cream stick strategy for active learning on the achievement of the female students at grade 10. - The researcher depend on the two equal groups with the, which requires the presence of the two groups, one experimental and the other control, the research community consists of all tenth grade literary students in the Erbil governorate center for the academic year 2020-2021. The sample of the research was 42 female students, randomly distributed to the experimental group, 21 students were taught according to the strategy of ice cream sticks, while the control group was taught according to the usual method. The researcher conducted the equivalence between the students of the two groups in the variables: the chronological age calculated in months, the marks of the students for the ninth grade in the academic year 2019-2020, the marks of the social subject for the previous academic year, and the intelligence quotient and academic achievement of the fathers and mothers. The researcher prepared (30) teaching plans by (15) according to the strategy of ice cream sticks and the same according to the usual method (used). The experiment began on 16/5/2021 and ended on 30/6/2021. It should be known that the researcher himself taught the students of the two groups. And the null hypothesis was set, which states (there is no statistically significant difference at the level (0.05) between the mean marks of the experimental group that was taught using the ice cream sticks strategy and the average marks of the control group that taught in the usual way (followed) in the post achievement test. The researcher used a test tool to measure the standardized achievement, which was prepared by (Ali Ahmed Hamad Amin, 2014) and the number of its items was (40) items of the type of multiple test. Its stability was confirmed by re-testing and after completion of the experiment and application. The researcher extracted the data and conducted the statistic with it using the statistic bag. (SPSS) In light of the results the researcher arrived at the following: 1- The experimental group that used the ice cream sticks strategy outperformed the control group that used the usual method (followed) in the material collection in favor of the experimental group. In light of the results, the researcher arrived at some conclusions.